THE EFFECTIVENESS OF SNAIL MUCUS (ACHATINA FULICA) AND CHITOSAN TOWARD LIMFOSIT PROLIFERATION IN VITRO - Harti, Agnes Sri; Murharyati, Atiek; S, Dwi Sulisetyawati; Oktariani, Meri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to assess the effectiveness of mucous and chitin slime cream against lymphocyte proliferation in vitro. Methods: The research methods include snail mucus isolation, snail mucus cream material preparation, and lymphocyte cell proliferation test of 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction method. Results: Lymphocyte cell proliferation test of MTT reduction method showed that chitosan 5% gave the most effective result toward lymphocyte proliferation activity compared to 100% snail slime and 5% snail slime cream. The 5% snail mucus cream 5% provides a higher proliferative activity than the 100% snail mucus. Positive control using Con A solution. Negative control was treatment without addition of test solution. The differences in lymphocyte proliferation activity were due to the presence of active compounds in chitosan, snail mucus, and snail slime cream that potentially increase lymphocyte proliferation. Significant differences in lymphocyte cell proliferation as Group K1, K2, K3, K4, K5, and K6. Conclusion: The effectiveness of snail and chitosan slime cream toward lymphocyte proliferation by in vitro that chitosan 5% gave the most effective result toward lymphocyte proliferation activity compared to 100% snail slime and 5% snail slime cream.